PENGARUH KOMUNIKASI ORGANISASI TERHADAP KUALITAS PELAYANAN BIDANG PENDIDIKAN MENENGAH DI KOTA BANDUNG (SUATU KASUS DI DINAS PENDIDIKAN KOTA BANDUNG) - Priatna, Ramdani (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
The reserach aims at analyzing the influence of organization communication on the high education service quality in Bandung City. It applies descriptive method and survey-explanatory method.. Descriptive method is used to describe all variables analyzed in this thesis. Surveyexplanatory method is used to illustrate the influence of organization communication variables on the high education service quality in Bandung City. The organization communication variablesconsist of organization communication climate and organization communication satisfaction. The result shows that the grade of organization communication influnce on Bandung City the high education service quality is determined by the variables of organization communication climate and organization communication satisfaction, which simultaneously contribute 44.30 %. The other 55.70 % is influenced by such fators as the availability of facility and work mechanism. Partially, the organization communication climate influences the education service quality as much as 42.10%. The other 57.90 % is influenced by such fators as the availability of facility and work mechanism. At the same time, organization communication satisfaction influences the educationservice quality as much as 30.60 %. The other 69.40 % is influenced by such fators as the availability of facility and work mechanism.